The soil fungal community of native woodland in Andean Patagonian forest: A case study considering experimental forest management and seasonal effects - Carron, Ayelen Inés; Garibaldi, Lucas Alejandro; Marquez, Sebastian; Fontenla, Sonia (Forest ecology and management, 2020)
•Woodland cover dominated by AM-plants and soil were similar to Patagonian forests.•Agaricales (Agaricomycets) and Helotiales (Leotiomycets) were the most abundant.•Humidity, EC, C, N, and P were modelers of the community at different taxonomic levels.•The seasons influenced the class and guild, but not the diversity of the community.•Saprotroph were the most abundant; followed by Pathogen and ECM (specially Cortinarius).•Woodland management only modified richness and phosphorus, they could be bio-indicators. Forest management can alter soil fungal communities which are important in the regulation of biogeochemical cycles and other ecosystem services. The current challenge of sustainable management is that management be carried out while preserving the bioecological aspects of ecosystems. Mixed Patagonian woodlands are subject to continuous disturbance (fire, wood extraction, and livestock), with unknown consequences for soil fungal communities. Our objective was to study the fungal community and the effects of an experimental forest management program, which combines harvesting and implantation, on the soil fungal communities in Patagonian woodland, in Argentina; considering contrasting seasons and soil parameters. At site level, the mixed woodlands appear to have greater soil cover with AM plants and soil chemical characteristics similar to other forest environments in the same region, with an intermediate fungal diversity value. When the seasonal effect was analyzed, no changes were observed in the fungal richness and diversity index, whereas modifications were recorded in the class level, in the ecological guilds, and in certain soil parameters; the inversion of phyla should be highlighted. Ascomycota and Basidiomycota were the predominant phyla, and presented a tendency to an inversion between seasons: Ascomycota fungi predominated in autumn, while Basidiomycota were more abundant in summer. The Glomeromycota were not well represented in this study. The most abundant classes were Agaricomycetes, followed by Leotiomycetes, Sordariomycetes, and Tremellomycetes, with some changes in the proportions between the two seasons, which could be related to certain soil characteristics. The most abundant orders in both seasons were Agaricales, Helotiales, Mortierellales, and Filobasidiales, correlated with some soil characteristics. The ordination analysis (NMDS) showed a correlation between taxonomic assignation and some soil characteristics, and only between class seasons. The most abundant ecological guild was saprotrophs (in both seasons: Hygrocybe, Mortierella, Cryptococcus), followed by plant pathogens (Ilyonectria, which increase in autumn); and the ectomycorrhizal symbiont (Hygrocybe in both seasons, while in summer Cortinarius, Clitopilus, and Geoglossum), all are related to C and N cycle. The only post-management changes observed in soil fungal community and chemical characteristics were in fungal richness (OTUs) and available phosphorus values; all the others (diversity indexes, taxonomy, and ecological guilds) were unaffected by this anthropic disturbance. It should be highlighted that available P and fungal species richness could be proposed as bioindicators. Future studies in native management programs, considering other aspects such as diversity of vegetation uses and system functions of the area will allow us to assess whether some of these changes are early bio-indicators of sustainable use and management.